Morfología de Prosaldius saccharidis Barber (Coleoptera: Curculionidae), Trujillo, Perú, 2017. - Cuzco Bobadilla, Cynthia Catherine (2018)
Prosaldius saccharidis Barber (Coleoptera: Curculionidae) "black weevil" is a potential pest that causes damages in the cultivation of sugarcane in the country. El objetivo del presente trabajo fue determinar las características de las diferentes fases biológicas de P. saccharidis. The biological states of the pest were obtained from ex-CEPCAM-UNT, in the laboratory were performed the dissection, assembly, observation and description using the Olympus SZX16 stereoscope, software: DP2-BSW-version 2.2. The egg presented an average length of 0.54 ± 0.03 mm; the larva III, an average length in head and body of 0.94 ± 0.02 and 4.36 ± 0.18 respectively; the pupa had an average length of 4.22 ± 0.21 mm. The head of the adult together with the prothorax presented an average length of 1.49 ± 0.15 mm. and the abdomen, 2.36 ± 0.14 mm. It’s concludes by determining the morphological characteristics of the different biological states of P. saccharidis, the sexual dimorphism, in the form of tergito VII, the esternitos, V, VI and genitalia of the adult.